Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a, ta có \(\cos^2\alpha\)+ \(\sin^2\alpha\)= 1
1/5 + \(\cos^2\alpha\)= 1
\(\cos^2\alpha\)= 4/5
\(4\cos^2\alpha\)+6 \(\sin^2\alpha\)= 4 . 4/5 + 6.1/5=22/5
b, \(\sin\alpha\)= 2/3
\(\sin^2\alpha\)= 4/9
\(\cos^2\alpha=\frac{5}{9}\)
\(5\cos^2\alpha+2\sin^2=\frac{5.5}{9}+\frac{2.4}{9}=\frac{33}{9}\)
#mã mã#
![](https://rs.olm.vn/images/avt/0.png?1311)
\(M=\frac{\frac{sina}{cosa}+\frac{cosa}{cosa}}{\frac{sina}{cosa}-\frac{cosa}{cosa}}=\frac{tana+1}{tana-1}=\frac{\frac{3}{5}+1}{\frac{3}{5}-1}=...\)
\(N=\frac{\frac{sina.cosa}{cos^2a}}{\frac{sin^2a}{cos^2a}-\frac{cos^2a}{cos^2a}}=\frac{tana}{tan^2a-1}=...\) (thay số bấm máy)
\(P=\frac{\frac{sin^3a}{cos^3a}+\frac{cos^3a}{cos^3a}}{\frac{2sina.cos^2a}{cos^3a}+\frac{cosa.sin^2a}{cos^3a}}=\frac{tan^3a+1}{2tana+tan^2a}=...\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=4\left(1-sin^2x\right)-6sin^2a=4-10sin^2a=4-10.\left(\frac{1}{5}\right)^2=...\)
\(tana+cota=3\Leftrightarrow\frac{sina}{cosa}+\frac{cosa}{sina}=3\Leftrightarrow\frac{sin^2a+cos^2a}{sina.cosa}=3\)
\(\Leftrightarrow\frac{1}{sina.cosa}=3\Leftrightarrow sina.cosa=\frac{1}{3}\)
\(C=cot^2a-cos^2a.cot^2a=cot^2a\left(1-cos^2a\right)=cot^2a.sin^2a\)
\(=\frac{cos^2a}{sin^2a}.sin^2a=cos^2a=1-sin^2a=1-\left(\frac{3}{4}\right)^2=...\)
Ta có \(\sin^2\alpha+\cos^2\alpha=1\Leftrightarrow\cos^2\alpha=1-\sin^2\alpha=1-\left(\frac{8}{17}\right)^2=\frac{225}{289}\)
Vậy B=\(4.\left(\frac{8}{17}\right)^2+3.\frac{225}{289}=\)\(\frac{931}{289}\)
huhu. Mẹ ơi! Làm sao thắng nó!!!